Rescuing Positive Freedom from Neo-Republican Attack - Seleme, Hugo Omar (2015)
This paper is structured into three sections. First, I will make a stylizedpresentation of the Berlinian matrix and freedom as non-domination as Pettitunderstands it. I aim to show that if one intends to present non-domination as aconception with elements borrowed from positive freedom, then it is necessary tounderstand positive freedom in terms of control-indeed Pettit has begun to present freedom as non-domination in terms of control. Once positive freedom is thus understood, a new type of positive freedom, hidden until now, emerges. Second, I will show why Pettit´s reasoning that freedom as non-domination is morally more attractive than populist positive freedom does not apply to this new type of positive freedom. Pettit has been successful in presenting a distinguishable conception of freedom as non-domination, but he has not offered any arguments to show that it is morally preferable to the type of positive freedom I present. Third, I will explain why freedom as institutional control is morally preferable to freedom as non-domination.